the Uji Toksisitas Ekstrak Etanol Kulit Batang Pala (Myristica fragrans Houtt) Terhadap Artemia salina Leach - Handayani, Virsa; Gazali, Anggun; -, Auliawati (Makassar Natural Product Journal (MNPJ), 2024)
ABSTRACT Nutmeg (Myristica fragrans Houtt) is a multipurpose plant that comes from the Myristicaceae family and has properties to treat indigestion, diarrhea, plague parasites and rheumatism. Nutmeg bark contains secondary metabolite compounds of alkaloids, flavonoids, triterpenoids, saponins, and tannins. This study aims to determine the toxicity effect and Lethal Concentration (LC50) value of ethanol extract of nutmeg stem bark (Myristica fragrans Houtt) on Artemia salina Leach larvae. The extraction method used was reflux using ethanol 96% solvent. The ethanol extract of Nutmeg bark (Myristica fragrans Houtt) was made with a concentration series of 250 ppm, 500 ppm, 1000 ppm, 1500 ppm and toxicity test was carried out using Artemia salina Leach larvae, then calculated the percent mortality of larvae using Probit analysis. The test results showed that ethanol extract of Nutmeg bark (Myristica fragrans Houtt) at concentration of 1500 ppm caused the highest larval mortality with a total of 29 larval deaths. Based on the results of the research, it can be concluded that the ethanol extract of nutmeg bark (Myristica fragrans Houtt) has a toxic effect on Artemia salina Leach larvae and the Lethal concentration (LC50) value of the ethanol extract of nutmeg bark (Myristica fragrans Houttt) is 226.986 µg/mL so it is in the toxic category. Keywords: Toxicity, Nutmeg bark (Myristica fragrans Houtt), Artemia salina Leach. ABSTRAK Tanaman pala (Myristica fragrans Houtt) merupakan tanaman multiguna yang berasal dari family Myristicaceae dan memiliki khasiat untuk mengobati gangguan pencernaan, diare, parasit wabah dan rematik. Kulit batang pala mengandung senyawa metabolit sekunder alkaloid, flavonoid, triterpenoid, saponin, dan tanin. Penelitian ini bertujuan untuk menentukan efek toksik dan nilai Lethal Concentration 50% (LC50) ekstrak etanol kulit batang pala (Myristica fragrans Houtt) terhadap larva Artemia salina Leach. Metode ekstraksi yang digunakan adalah refluks dengan menggunakan pelarut etanol 96%. Ekstrak etanol kulit batang pala (Myristica fragrans Houtt) dibuat larutan uji dengan seri konsentrasi 250 ppm, 500 ppm, 1000 ppm, 1500 ppm dan dilakukan pengujian toksisitas dengan menggunakan larva Artemia salina Leach, kemudian dihitung persen kematian larva menggunakan analisis probit. Hasil pengujian menunjukkan bahwa ekstrak etanol kulit batang pala (Myristica fragrans Houtt) pada konsentrasi 1500 ppm menyebabkan kematian larva tertinggi dengan total kematian larva sebanyak 29 ekor. Berdasarkan hasil penelitian yang telah dilakukan dapat disimpulkan bahwa ekstrak etanol kulit batang pala (Myristica fragrans Houtt) memberikan efek toksik terhadap larva Artemia salina Leach dan nilai Lethal concentration (LC50) pada ekstrak etanol kulit batang pala (Myristica fragrans Houttt) yaitu 226,986 ɥg/mL sehingga masuk kategori toksik Kata Kunci : Toksisitas; Kulit batang pala (Myristica fragrans Houtt); Artemia salina Leach.